Analysis of calculations, deductions, deposits and reporting income tax (PPh) article 21 for employees at CV. Putra Jaya - Winarsih, Tri; Qosim, Qosim (Institute of Accounting Research and Novation (IARN), 2024)
Income Tax Article 21 or what can be called Income Tax Article 21 is a tax on income in the form of salary, wages, honorarium, allowances and other payments in any name and in any form in connection with work or position, services and activities carried out by individuals subject to domestic taxation. . The purpose of this research is to determine the process of calculating, withholding, depositing and reporting Income Tax Article 21 for CV employees. Putra Jaya with reference to the provisions of PMK 168 of 2023 concerning instructions for implementing tax deductions on income in connection with work, services or personal activities. This research uses a descriptive method with a quantitative and qualitative approach. The research results show that the calculation of deductions, deposits and reporting of PPh Article 21 for employees has been implemented by CV. Putra Jaya is in accordance with PMK 168 of 2023.